2014
DOI: 10.1128/aem.01689-14
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Autoinducer-Dependent and -Independent Heterogeneous Gene Expression in Sinorhizobium fredii NGR234

Abstract: Populations of genetically identical Sinorhizobium fredii NGR234 cells differ significantly in their expression profiles of autoinducer (AI)-dependent and AI-independent genes. Promoter fusions of the NGR234 AI synthase genes traI and ngrI showed high levels of phenotypic heterogeneity during growth in TY medium on a single-cell level. However, adding very high concentrations of N-(3-oxooctanoyl-)-L-homoserine lactone resulted in a more homogeneous expression profile. Similarly, the lack of internally synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…The upregulation of the AI systems in the background of the AI synthase deletion mutants was in part verified by population-wide transcriptome data (31). Not only the AI themselves but also the addition of crude plant root exudates or octopine as a plant-released molecule caused a more homogenous expression of the AI systems (30). Part of this study was confirmed by tests with the close relative Sinorhizobium meliloti using a sinI reporter gene fusion (32).…”
Section: Bacterial Qs: a System Thought To Coordinate Cells Instead Osupporting
confidence: 49%
See 3 more Smart Citations
“…The upregulation of the AI systems in the background of the AI synthase deletion mutants was in part verified by population-wide transcriptome data (31). Not only the AI themselves but also the addition of crude plant root exudates or octopine as a plant-released molecule caused a more homogenous expression of the AI systems (30). Part of this study was confirmed by tests with the close relative Sinorhizobium meliloti using a sinI reporter gene fusion (32).…”
Section: Bacterial Qs: a System Thought To Coordinate Cells Instead Osupporting
confidence: 49%
“…Part of this study was confirmed by tests with the close relative Sinorhizobium meliloti using a sinI reporter gene fusion (32). Further investigations in S. fredii NGR234 indicated that quorum quenching genes and a type IV pilus gene cluster showed phenotypic heterogeneity that was independent of the influence of cell-cell communication signals (30).…”
Section: Bacterial Qs: a System Thought To Coordinate Cells Instead Omentioning
confidence: 58%
See 2 more Smart Citations
“…While in general it is assumed that a homogeneous expression of these genes occurred throughout an isogenic population, there is now initial evidence that this may not be the natural situation. Instead, a fraction of the NGR234 genes are most likely heterogeneously expressed on a single-cell level (98). In the light of these novel findings, future work will now have to elucidate the complex pattern of gene expression and regulation on a single-cell level in this fascinating microorganism.…”
Section: Fig 2 Venn Diagram Showing the Overlap Of Differentially Expmentioning
confidence: 99%